Legal Analysis of the Impact of Port Development on Marine Ecosystems - Priliska, Jedyzha Azzariel (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research aims to identify the impacts of ports and their legal regulations, and to evaluate the efforts that must be made by the government in responding to the impacts of port development. By using qualitative methods to collect data, further studies on existing regulations and problems. The research process includes understanding the topic and scope, searching for references, collecting data analyzing and make conclusion. This research provides an explanation that port development in Indonesia is still lacking in paying attention to the safety of marine ecosystems. Although the law already exists, further supervision and monitoring of port management must be stricter to avoid things that cause damage